Clinical outcomes of cyclin-dependent kinase 4–6 (CDK 4–6) inhibitors in patients with male breast cancer: A multicenter study. (December 2022) - Yıldırım, Hasan Çağrı; Mutlu, Emel; Chalabiyev, Elvin; Özen, Miraç; Keskinkılıç, Merve; Ön, Sercan; Çelebi, Abdussamet; Dursun, Bengü; Acar, Ömer; Kahraman, Seda; Aykan, Musa Barış; Kaman, Ömür; et al.
Abstract: Background: Since breast cancer is less common in men than in women, data on the use of new therapeutic agents, including cyclin-dependent kinase 4–6 (CDK 4–6) inhibitors, are limited in patients with metastatic hormone receptor positive (HR+), human epidermal growth factor receptor 2-negative (HER2-) male breast cancer. Therefore; we aimed to investigate the treatment responses of metastatic HR+, HER2-male breast cancer patients treated with CDK 4–6 inhibitors in a multicenter real-life cohort. Methods: Male patients with a diagnosis of HR+ and HER2-metastatic breast cancer, treated with any CDK 4–6 inhibitor, were included in the study. Demographic and clinical characteristics of the patients were recorded. We aimed to determine progression-free survival (PFS) time, response rates and drug related side effects. Results: A total 25 patients from 14 institutions were recruited. The mean age at diagnosis was 57 years. Median follow-up was 19.53 (95% CI: 14.04–25.02) months. The overall response rate was 60%. While the median PFS was 20.6 months in the whole cohort, it wasn't reached in those using CDK 4–6 inhibitors in first line and 10 months in the subsequent lines (p:0.009). No new adverse events were encountered. Conclusion: In our study, we found that CDK 4–6 inhibitors are effective and safe options in men with HR+ and HER2-metastatic breast cancer as in women. Our results support the use of CDK 4–6 inhibitor-based combinations in the first-line treatment of HR+ and HER2-metastatic male breast cancer. Highlights: CDK 4–6 inhibitors are effective and safe agents for male patients. They should be used in the first line treatment for the most effective results. Palbociclib had numerically better, statistically similar progression-free survival time to ribociclib.